2017
DOI: 10.1007/s12197-017-9390-1
|View full text |Cite
|
Sign up to set email alerts
|

CEO ability and firm performance: Stock market and job market reactions

Abstract: Does the stock market and job market evaluate a CEO based on the performance of his/her previous employer? We answer this question by examining a sample of 48 CEOs who voluntarily resigned from old firms to obtain similar positions with new firms. Using a sample of CEOs that voluntarily resigned from S&P 500 firms during 2004-2012, we find that the stock market's reactions to announcements of them resigning from old firms and being hired by new firms depend on how well the old firms had performed. The market i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The relationships that we found between BoD characteristics and investment efficiency are consistent with the argument that greater BIND (Fauver et al, 2017; Rashid, 2018; Setia‐Atmaja et al, 2009), adequate performance compensation to the board (Faulkender et al, 2010; Lai & Liu, 2018; Nguyen, 2014), short‐term CEO career concerns (Jun & Min, 2017; Mukherjee & Nguyen, 2018), and non‐dual board leadership (Broye et al, 2017; Nasr & Ntim, 2018) significantly limit managers' opportunistic investment behaviour, and accordingly, these characteristics ultimately improve corporate investment efficiency.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The relationships that we found between BoD characteristics and investment efficiency are consistent with the argument that greater BIND (Fauver et al, 2017; Rashid, 2018; Setia‐Atmaja et al, 2009), adequate performance compensation to the board (Faulkender et al, 2010; Lai & Liu, 2018; Nguyen, 2014), short‐term CEO career concerns (Jun & Min, 2017; Mukherjee & Nguyen, 2018), and non‐dual board leadership (Broye et al, 2017; Nasr & Ntim, 2018) significantly limit managers' opportunistic investment behaviour, and accordingly, these characteristics ultimately improve corporate investment efficiency.…”
Section: Resultssupporting
confidence: 84%
“…Prior literature confirmed that CEOs' careers depend on their past achievements and current performance. Mukherjee and Nguyen (2018) concluded that the stock market evaluates CEOs by grouping them – according to their previous performance – into better and good CEOs. They found that better CEOs could get a new job much faster, and their new companies were rewarded with higher long‐term returns.…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Bentley et al (2013), Custódio et al (2013), Higgins et al (2015) and Mukherjee and Nguyen (2018), we include several CEO"s and firm"s characteristics that are potentially correlated with general managerial ability, strategy and firm performance and risk as control variables. We describe these variables below.…”
Section: Control Variablesmentioning
confidence: 99%
“…Jung and Subramanian (2017) found that CEO talent is more important in more competitive markets with greater product substitutability, which highlights the effect of CEO ability on firm's strategic actions and competitiveness. More able CEOs are also better able to manage complex relationships with salient stakeholder groups and other influential secondary stakeholders such as the media and NGOs (Mukherjee and Nguyen, 2018). The unique set of abilities and extensive knowledge of more able CEOs allows them to better formulate and implement an efficient CSR strategy.…”
Section: Csr and Firm Performancementioning
confidence: 99%